Pemberdayaan Pokdarwis Kampung Gambut Melalui Program CSR PT Pertamina IT Pontianak, Kelurahan Siantan Hilir - Ridwan, Tri Rizky Imam; Sikwan, Agus; Harahap, Reiki Nauli; Musa, Dahniar TH; Marini, Marini; Nugroho, Waskito (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe the early history of the formation of the Kampung Gambut Tourism Awareness Group, analyze the empowerment program implemented through PT Pertamina IT Pontianak's CSR program for the managers of the Kampung Gambut Tourism Awareness Group, and examine the impact on the members of the Kampung Gambut Tourism Awareness Group who have participated in the empowerment program implemented by PT Pertamina IT Pontianak's CSR. In this thesis, the author seeks to explain the initial process of forming the Kampung Gambut Tourism Awareness Group, analyze the empowerment program implemented by PT Pertamina's CSR program for the members of the Kampung Gambut Tourism Awareness Group, and assess the impact on the members of the Kampung Gambut Tourism Awareness Group who have participated in the empowerment program provided. The data collection techniques used in this study include observation, interviews, and documentary studies. The theory used in this study is the empowerment theory by Jim Ife. The results of this study indicate that the initial formation of the Kampung Gambut Tourism Awareness Group was driven by the collective desire of the community to utilize their natural resources. Additionally, the empowerment programs implemented by PT Pertamina IT Pontianak's CSR initiative provided programs tailored to the community's needs, fostering the development of the community, nature, and the environment simultaneously. Meanwhile, the impacts felt by members of the Kampung Gambut Tourism Awareness Group after participating in and implementing the empowerment program of PT Pertamina IT Pontianak's CSR have shown changes in economic, social, and environmental aspects. These impacts emerged alongside the community's increasing understanding of tourism management in Kampung Gambut.